Endovascular therapy of isolated posterior cerebral artery occlusion stroke with and without general anesthesia - Berberich, Anne; Herweh, Christian; Qureshi, Muhammad M.; Strambo, Davide; Michel, Patrik; Räty, Silja; Abdalkader, Mohamad; Virtanen, Pekka; Gadea, Marta Olive; Ribo, Marc; Psychogios, Marios-Nikos; Nguyen, Anh; et al. (Journal of neuroInterventional surgery, 2025)
Background: The optimal anesthetic strategy for endovascular therapy (EVT) in acute ischemic stroke is still under debate. The aim of this study was to compare the clinical outcomes of patients with isolated posterior cerebral artery (PCA) occlusion stroke undergoing EVT by anesthesia modality with conscious sedation (non-GA) versus general anesthesia (GA). - Methods: Patients from the Posterior CerebraL Artery Occlusion (PLATO) study were analyzed with regard to anesthetic strategy. GA was compared with non-GA using multivariable logistic regression and inverse probability of weighting treatment (IPTW) methods. The primary endpoint was the 90-day distribution of the modified Rankin Scale (mRS) score. Secondary outcomes included functional independence or return to Rankin at day 90, and successful reperfusion, defined as expanded Thrombolysis in Cerebral Infarction (eTICI) 2b to 3. Safety endpoints were symptomatic intracranial hemorrhage and mortality. - Results: Among 376 patients with isolated PCA occlusion stroke treated with EVT, 183 (49%) had GA. The treatment groups were comparable, although the GA group contained more patients with severe stroke and lower posterior circulation Alberta Stroke Program Early CT Score (pc-ASPECTS). On IPTW analysis, there was no difference between groups with regard to ordinal mRS shift analysis (common OR 0.89, 95% CI 0.53 to 1.51, P=0.67) or functional independence (OR 0.84, 95% CI 0.50 to 1.39, P=0.49). There were greater odds for successful reperfusion with GA (OR 1.70, 95% CI 1.17 to 2.47, P=0.01). Safety outcomes were comparable between groups. - Conclusion: In patients with isolated PCA occlusion undergoing EVT, patients treated with GA had higher reperfusion rates compared with non-GA. Both GA and non-GA strategies were safe and functional outcomes were similar.